Anna and Saihou - Eine Liebesgeschichte - Dismer, Denise (Germany, 2013)
Saihou is an asylum-seeker from Gambia living in Germany. He would like to marry his girlfriend Anna but the authorities refuse to issue the required documents. Then comes the news that Saihou will be deported.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films